3,3,4,4,5,5-Hexafluoro-1,2-bis[5-(2-fluoro-4′-undecyloxybiphenyl-4-yl)-2-methyl-3-thienyl]cyclopentene - Frigoli, Michel (International Union of Crystallography, 2008)
The title compound, C(61)H(68)F(8)O(2)S(2), is a photochromic liquid crystal based on diarylethene as photoswitchable unit. The F atoms connected to the benzene rings are disordered over two positions; the site-occupation factors refined to 0.830 (3)/0.170 (3). The molecule adopts a photo-active antiparallel conformation and the distance between the two reactive C atoms of the thiophene rings is 3.448 (3) Å. The dihedral angles between the central cyclopentene ring and the adjacent thiophene rings are 43.56 (3) and 48.58 (3)°. These structural elements exhibit a suitable geometry for photochromic behaviour in the crystalline state.